Strengthening IRE Teacher Competencies for Character Education and SDGs Realization - Endang Switri; M. Sirozi; Annisa Astrid; Rozi Irfan Rosyadi; Meguellati Achour; Hamidah; Muhammad Torik (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study aims to examine the role of Islamic Religious Education (IRE) teachers' competencies in integrating character education to support the achievement of Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education) and SDG 16 (Peace, Justice, and Strong Institutions), in Ogan Ilir Regency. Theoretical framework: The study draws on Lickona’s character education theory (cognitive, affective, conative dimensions) and Muslich’s teacher competency framework (pedagogic, professional, personality, social aspects) for integrating character education into IRE learning. Literature review: Previous research underscores the importance of character education, its integration challenges, and the essential role of IRE teachers as moral role models, though competencies in character education vary. Methods: A mixed-methods approach was used, involving quantitative (competency tests) and qualitative (interviews, observations, document analysis) data from 70 IRE teachers in Ogan Ilir Regency. Data were analyzed with SPSS and thematic coding. Results: The study found that IRE teachers' competencies in planning and implementing character education were generally adequate, but significant gaps existed in the evaluation of character education. Most teachers demonstrated sufficient competencies in integrating character values during planning and implementation phases, but the evaluation of character education was weak, with limited use of standardized assessment tools. Implications: The study highlights that IRE teachers face challenges such as limited time, resources, and training. Novelty: This research is among the first to analyze IRE teachers' competencies in integrating character education in Ogan Ilir Regency, offering new insights into how teacher competencies support sustainable development goals in education.